Metagenomic and culture-based genomics reveal virulence and resistance risks in Manila clam microbiomes - Yaling Wang; Linan He; Xing Hu; Yuhan Guan; Xiangnan Chen; Jiahui Du; Jiayan Chen; Chensheng Ma; Lianwei Ye (Food Microbiology, 2026)

AUV path planning method for data collection in underwater wireless sensor network - Zongyu He; Qian Sun; Yibing Li; Linan Ma; Yujie Huang (Ocean Engineering, 2026)

Investigation of hydrate formation and flow characteristics within multiphase transmission pipelines employing a constant pressure visualization loop system - Xi Wang; Kaibang Liu; Shouyi Ma; Linan Guan; Zherui Chen; Yan Qin; Jingyue Sun; Cong Chen (Gas Science and Engineering, 2025)

Teleost HMGB1 paralogues mediate protective autophagy by interacting with NOD2 and ATG16L1 and activating ROS/Akt/mTOR pathway against Aeromonas hydrophila infection - Dan Wang; Linan Chen; Xiaoyu Ma; Zhe Wang; Hong Zhou (Fish & Shellfish Immunology, 2025)

Naturally Occurring Epialleles and Their Roles in Response to Climate Change in Birch - Bowei Chen; Tianxu Zhang; Yile Guo; Lesheng Cao; Xu Zhang; Shahid Ali; Renyi Ma; Linan Xie; Jiang Wang; Gaurav Zinta; Shanwen Sun; Guifeng Liu; et al. (Molecular Ecology, 2025)
Epigenetics has been proposed to be an important mechanism that enables plant species to respond and adapt to environmental and climatic fluctuations and is sometimes entirely uncoupled from genetic variation. Nevertheless, the extent of this uncoupling and the contribution of epigenetics to plant responses to global climate change have not been well studied, particularly in forest trees. Here, we generated a high‐quality genome assembly for Betula platyphylla , a key pioneer species in temperate and boreal forest ecosystems, one of the most sensitive areas to global warming. Extensive multi‐omics sequencing of naturally white birch across the 48 provenances captured their full scope of temperate/boreal forests in Northeast China. Using a genome‐wide association study (GWAS), it was shown that over 55% of differentially methylated regions (DMRs) were spontaneous, independent of genetic factors. More than 30% of the spontaneous DMRs were significantly associated with gene expression, that is, potential epialleles, which are primarily involved in metabolism and responses to abiotic stresses; and 1819 of these epialleles were significantly associated with bio‐climatic variables (i.e., climatic epialleles, cEpialleles). Integrating these cEpialleles into a gradient modelling framework revealed that the natural populations of Asian white birch at high altitude/latitude might be most vulnerable to future climates. Our findings highlight the importance of integrating epigenomic and climatic data sets to forecast the adaptive capacity of a key forest species to rapid climate change.

Integrated response surface and machine learning approach: Experimental optimization and DFT analysis for NaN3 removal via NaClO oxidation - Yunfeng Tan; Jiangzhou Qin; Shengquan Chang; Shengqiang Ma; Linan Su; Nengsheng Liu; Quanlin Zhao; Xintao Wang; Chenxi Li; Jinmao Ma; Kun Wu; Zhengfang Ye (Journal of Water Process Engineering, 2025)

A putative Na+/H+ antiporter BpSOS1 contributes to salt tolerance in birch - Minghui Zhang; Mingke Wu; Tao Xu; Junfeng Cao; Zihui Zhang; Tianxu Zhang; Qingyi Xie; Jiang Wang; Shanwen Sun; Qingzhu Zhang; Renyi Ma; Linan Xie (Plant Science, 2024)

Revealing new insights: Two-center evidence of microplastics in human vitreous humor and their implications for ocular health - Yizhou Zhong; Yuhang Yang; Linan Zhang; Dahui Ma; Kailiang Wen; Jiachun Cai; Zhanmou Cai; Cui Wang; Xiaoyan Chai; Jingwen Zhong; Boxuan Liang; Yuji Huang; et al. (Science of The Total Environment, 2024)

Characteristics of indoor and outdoor fine particles in heating period at urban, suburban, and rural sites in Harbin, China - Wenxu Fang; Weiwei Song; Liyan Liu; Guangnian Chen; Linan Ma; Yuxuan Liang; Yujie Xu; Xueying Wang; Yehao Ji; Yu Zhuang; Amadou Hima Boubacar; Yifan Li (Environmental Science and Pollution Research, 2020)

An estimating function approach to linkage heterogeneity - HE GAO; YING ZHOU; WEIJUN MA; HAIDONG LIU; LINAN ZHAO (Journal of Genetics, 2013)